Hadis Hadis Pendidikan Laki Laki dan Perempuan - Hesti Humairoh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article discusses the understanding of the hadiths of the Prophet Muhammad SAW relating to the education of men and women from a gender equality perspective. Starting from the reality of unequal access to education that still exists in society, this paper examines how Islam, through its hadiths, provides a normative basis for the principles of justice and equal educational rights for all genders. The research employs a qualitative approach using literature review and hermeneutic analysis methods, as well as the mubadalah approach in interpreting the hadiths. The findings reveal that Islam not only encourages men but also women to seek knowledge and eliminates all forms of gender-based discrimination. By understanding the hadiths in their contextual framework, education can serve as a tool for social transformation toward a just, civilized, and equitable society.